What children need to be happy, confident and successful : step by step positive psychology to help children flourish - Hooper, Jeni (Jennifer Susan), 1952- (Jessica Kingsley Publishers, 2012)
What makes children happy, confident and successful? How can you help a child to flourish? Their environment is important, but the real difference is in your hands - every adult has the tools to help a child achieve psychological wellbeing. This book provides a practical model for helping children flourish and achieve their personal potential in every area of their lives. Drawing on ideas from positive psychology and child development theory, the model explores the five key areas of wellbeing: personal strengths, emotional wellbeing, positive communication, learning strengths, and resilience.